2020
DOI: 10.18805/lr-4173
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability, Components of Genetic Variance and Heterotic Response in Faba Bean (Vicia faba L.)

Abstract: The present investigation was carried out at the Students’ Instructional Farm, Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya to evaluate a line x tester set of 45 hybrids (F1’s) and their 18 parents alongwith two checks for twelve characters. Forty-five crosses were constituted in Rabi, 2016-2017, whereas parents and crosses were evaluated in a yield trial in Rabi 2017-2018, in a randomized complete block design of three replications. Results revealed highly significant variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…The same results were obtained by Lal et al (2020) and Neda et al (2021) [31,32], who reported that the faba bean cultivar Giza 843 was the highest in terms of morphological traits such as number of branches per plant and the weight of 100 seeds. The hybridization of different parents isolates useful recombinants in the segregating generations [33].…”
Section: Mean Performancesupporting
confidence: 84%
“…The same results were obtained by Lal et al (2020) and Neda et al (2021) [31,32], who reported that the faba bean cultivar Giza 843 was the highest in terms of morphological traits such as number of branches per plant and the weight of 100 seeds. The hybridization of different parents isolates useful recombinants in the segregating generations [33].…”
Section: Mean Performancesupporting
confidence: 84%